Features Of Translation Of Documents And Official Texts (Diversity Research: Journal of Analysis and Trends, 2024)
The article presents the main features of the translation of official business texts and in the opposite combination in the context of the cultures of the host and source languages. The main difficulties that a translator encounters when translating documents are associated with terminology, lexical transformations, overcoming differences in translation in the legal systems of the languages of the original and the language of the host culture.